1999
DOI: 10.1055/s-2007-978811
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cardiac Glucose Transport by Thioctic Acid and Insulin

Abstract: Thioctic acid (alpha-lipoic acid) has been shown to improve insulin-regulated glucose disposal in animal models of insulin resistance and type 2 diabetic patients. In the present study, we have used isolated adult ventricular cardiomyocytes in order to analyze 1) direct effects of this compound on glucose uptake in a primary muscle cell, and 2) the interaction with the insulin signalling cascade. Both insulin and thioctic acid (2.5 mM) induced a rapid increase in 3-O-methylglucose transport to 322+/-43 and 385… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
1
15
1
Order By: Relevance
“…However, in that study, the LA effect on glucose transport was observed at 10-fold higher concentrations of LA (i.e., millimolar or greater) than the effective concentrations reported here and in a previous study (21). Similarly, a direct stimulatory effect on glucose transport in response to a millimolar concentration of LA was recently reported in isolated cardiac myocytes (32). In contrast, in both the present study with L6 cells and the earlier study with 3T3-L1 adipocytes (21), only a small direct effect of LA on glucose transport could be detected, whereas major effects were observed in cells that had been subjected to oxidative stress.…”
Section: Insulin Resistance and ␣-Lipoic Acidcontrasting
confidence: 48%
“…However, in that study, the LA effect on glucose transport was observed at 10-fold higher concentrations of LA (i.e., millimolar or greater) than the effective concentrations reported here and in a previous study (21). Similarly, a direct stimulatory effect on glucose transport in response to a millimolar concentration of LA was recently reported in isolated cardiac myocytes (32). In contrast, in both the present study with L6 cells and the earlier study with 3T3-L1 adipocytes (21), only a small direct effect of LA on glucose transport could be detected, whereas major effects were observed in cells that had been subjected to oxidative stress.…”
Section: Insulin Resistance and ␣-Lipoic Acidcontrasting
confidence: 48%
“…This stimulatory effect is associated with an increase of PI 3-kinase and protein kinase B (Akt) activity. 9,10,14,28 ALA, like insulin, has been shown to increase intrinsic activity of glucose transporters. Activation of glucose transporters may be mediated by p 38 mitogen-activated protein kinase (MAPK), perhaps via a pathway independent of PI 3-kinase.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies have provided evidence that R-(+)-ALA can specifically activate two important molecules of the insulin signaling pathway-insulin receptor substrate-1 (IRS-1) protein and phosphatidylinositol 3-kinase (PI 3-kinase) with subsequent enhancement of glucose uptake via the glucose transporter system in skeletal muscle and adipocytes. 9,10 Thioctic acid has been shown to improve insulin sensitivity in cell cultures of skeletal muscles, 9,11-13 cardiomyocites, 14 and 3T3L1 adipocytes. 9,10 ALA has been found to increase insulin sensitivity in animal models of type 2 diabetes and insulin resistance in obese and lean Zucker rats.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies conducted in insulin responsive cells in culture demonstrated that LA rapidly stimulates glucose uptake by activating elements of the insulin signaling pathway (10,11). Insulin action is initiated by insulin binding to the extracellular ␣-subunit of the insulin receptor (IR), which transmits a transmembrane signal activating the intracellular tyrosine kinase domain of the ␤-subunits (12,13).…”
mentioning
confidence: 99%